Self-administered faecal occult blood tests do not increase compliance with screening for colorectal cancer: results of a randomized controlled trial. - Verne, J; Kettner, J; Mant, D; Farmer, A; Mortenson, N; Northover, J (1993)
In the UK, compliance with conventional faecal occult blood (FOB) tests such as Haemoccult is about 50% in the general population. It has been postulated that characteristics of the performance of conventional tests, in particular the need for dextrous gathering and manipulation of faeces, delay in receiving results, and the recommended dietary restrictions, may all diminish compliance. New FOB tests have been developed, popularly termed 'magic toilet paper' tests, which not only minimize faecal manipulation but are also self-reported. Compliance rates with two self-administered faecal occult blood tests (Early Detector and Coloscreen Self-Test) were compared with Haemoccult in a randomized trial involving 1,842 subjects aged 40-74 years. Use of self-administered FOB tests did not increase compliance significantly, with rates of 52.1% for Early Detector, 50.6% for Coloscreen and 49.1% for Haemoccult. Moreover, dietary restriction did not reduce compliance significantly (restricted 49.3%, unrestricted 51.8%). A wide variation (from 1.3% to 21.4%) in positivity rates was observed which was dependent on which of the three tests was used and whether dietary restrictions were applied. Since the physical aspects of test performance do not appear to determine an individual's decision to be screened, self-administered tests will not overcome the problem of poor compliance with FOB screening.